Back pain in Optimist sailors - Kostański, Leszek; Frąckowiak, Magdalena; Pospieszna, Barbara (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Back pain syndromes occur in 30-40% of kids and adolescents, aged 7-17 years, with prolonged sitting position or leisure time activities as usually mentioned possible causes. Sailing is a multifaceted sport, with relatively long periods of static positions and quasi-isometric muscle overload. Back pain in sailing results from either sailing it-self or from boat-related activities. Aim of Study. The aim of this study was to investigate the back pain epidemiology and etiology in Optimist dinghy sailing. Material and Methods. Eighty four optimist sailors (60 boys and 24 girls; 11 to 15 years) and their 18 coaches were surveyed, using 23 and 9 points questionnaires, respectively. Results. As much as 43% of analyzed Optimist sailors sensed back pain during the sailing season. Mainly thoracic and lumbosacral pain occurred during on-land boat-related activities and while sailing. On average, the sensed pain was occasional, lasting usually more than three months, of stabbing or radiating type and intensity of 2-6 on 10-point scale. Only six respondents underwent adequate physical examination and treatment. All trainers declared caring about their sailors’ need for healthy development, however 85% of them do not recommend, as a recovery strategy, the use of physio or kinesio-therapy, and 30% omit implementing special exercises related to spinal pain prophylactics and/or compensation. The trainers are not informed or informed occasionally about pain sensed by their trainees. Conclusions. There is the considerable need for the development of educational program of preventive and/or compensatory character to introduce in polish Optimist sports clubs.
Keywords: sailing; youth; pain; boat-related activities